La empresa socialmente responsable: una propuesta de autoevaluación - Alcabés, Nissim (2005)
The author proposes that corporations should self-evaluate the degree to which their performance towards their personnel, society and the nation is rated as socially responsible. He suggests 10 self-evaluation variables and a final overarching criterion. Quoting professor Sumantra Ghoshal, the author points to the need to review theoretical concepts that may have somehow dehumanized corporate management.